Gold Standard for Diagnosis of DPN - Yu, Yongchun (Frontiers in Endocrinology, 2021)
Diabetic peripheral neuropathy (DPN) is a common complication of diabetes mellitus. It often causes symmetrical paresthesia, loss of sensation and hyperalgesia. Without early intervention, it might lead to diabetic foot ulceration, gangrene and subsequent amputation in people with diabetes. DPN is an insidious disease and often underdiagnosed. This paper reviews the current national and international prevalence of DPN, screening methods for early DPN, including quantitative sensory measurement, neurological function scoring system, confocal microscopy and high-frequency ultrasound, and summarizes the related research progress, clinical application and development prospects of these methods in recent years.